Decomposição e liberação de macronutrientes e características físicas químicas de solo sob efeito de palhada de aveia sob diferentes manejos - Egewarth , Jonas Francisco (2020)
The Crop Livestock Integration System (ILP) follows the precepts of planned diversification, mixing two activities, agricultural and livestock, in more efficient and effective ways within the same area. For a good implantation and maintenance of the No-Till System (SPD) it is important to protect the soil with mulch, and the cultivation of cover plants in the winter period can mitigate the restrictive effect of soil compaction in summer cultivation. Thus, the objective of the present work was to evaluate the decomposition of the remaining straw of oat cultivars submitted to different managements, during the cultivation of corn for silage intercropped with brachiaria, as well as to observe the effect of these associations of cultivars and managements on physical characteristics. and concentration of carbon and nitrogen in the soil. The work was divided into two experiments. The first consisted of the evaluation of the residual straw decomposition of three oat cultivars, submitted to three different managements (“IAPAR 61 IBIPORÃ” hay (61F), “IAPAR 61 IBIPORÃ” grazed (61P), “IAPAR 61 IBIPORÃ” for cover (61SM), “Embrapa 139 (Fog)” hay (139F), “Embrapa 139 (Fog)” grazed (139P), “Embrapa 139 (Fog)” for cover (139SM), “Esmeralda IPR 126” hay (EF), “Esmeralda IPR 126” grazed (EP) and “Esmeralda IPR 126” for cover (ESM)), through the model of plots subdivided over time, through the method of decomposition bags (Litter bags), which were carried out at 0, 15, 30, 60, 90 and 108 days after sowing the corn crop for silage intercropped with brachiaria (Urochloa brizantha), with 03 replicates. As for the evaluations, the amount of residual straw, organic matter, carbon, nitrogen, carbon / nitrogen, phosphorus and potassium was determined. The results obtained from this experiment allow us to state that the rate of decomposition of oats is dependent on meteorological factors and its initial mass, that is, the greater its initial mass, the greater the time and effectiveness of mulch on the soil. The release of nutrients is also variable and dependent on the initial mass and edaphoclimatic conditions. The second experiment followed the strip model, and consisted of the evaluation of the effect of the residual straw of the nine combinations of oats and handling on the physical characteristics and the total organic carbon and total nitrogen content of the soil and its stocks. In this experiment, grazing did not interfere in soil compaction when managed and it can have a beneficial effect on subsurface. The different contribution of mass does not interfere in the concentration of carbon and nitrogen in the short term. Each cultivar can interfere differently in the resistance to penetration in subsequent crops, mainly in the depth of the most compacted layer.